Web-Based Decision Support System for Internship Placement Recommendations - Arif Faizin; Duabari Silas Aziaka (CV. Laskar Karya, 2026)
Internship placement is a critical component of vocational education aimed at improving students’ competencies and readiness for professional environments. However, internship placement processes in many institutions are still conducted manually, resulting in mismatches between student competencies and institutional requirements, reduced placement accuracy, and inefficient administrative procedures. This study proposes a web-based decision support system to improve the accuracy, objectivity, and efficiency of internship placement. The system integrates structured student data, institutional requirements, and evaluation criteria into an automated matching mechanism to generate placement recommendations. The development process includes data collection, system design, implementation, and testing to ensure functionality and usability. The system was evaluated using functional testing and user acceptance evaluation involving administrators, teachers, and students. The results demonstrate that the system operates effectively in managing data, calculating compatibility scores, and generating accurate placement recommendations. User evaluation indicates that the system improves administrative efficiency, transparency, and placement accuracy compared with manual methods. The proposed system provides a practical solution for managing internship placement and supports data-driven decision-making in educational institutions. The findings also indicate the potential for further development through integration with predictive analytics and broader institutional deployment to support digital transformation in educational management.